AI-Powered Innovations in Digestive Surgery: Current Evidence and Future Perspectives - A Systematic Literature - Napitupulu, Rudi Pandapotan; Ardli, Ghaly Khaidar; Ramadhani, Muhammad Rizky; Dira, Neysa Ornella; Sari, Andini Kartika (Riviera Publishing, 2025)
Artificial Intelligence (AI) is transforming the field of digestive surgery, offering significant advancements in diagnostic accuracy, surgical precision, and perioperative management. Technologies such as machine learning (ML) and deep learning (DL) enhance surgical outcomes by identifying complex patterns in data, supporting real-time decision-making, and improving personalized patient care. This study aims to systematically evaluate the current applications, challenges, and future potential of AI-powered innovations in digestive surgery. A systematic literature review was conducted following PRISMA guidelines. The search utilized databases including Scopus, PubMed, Google Scholar, Crossref, and Web of Science. Keywords like